Leaching Kinetics of Metallic Silver Using Di-ammonium Tartrate and Hydrogen Peroxide Solution as a Greener Substitute for Cyanide - Aydogan, Salih; Abdelraheem, Mohamed Taha Osman; Ali, Babiker; Boyrazli, Mustafa (Springer, 2024)
The kinetic of dissolving pure metallic silver in di-ammonium tartrate with a hydrogen peroxide solution is discussed in this article. The effects of temperature, di-ammonium tartrate concentration, hydrogen peroxide concentration, and rotation speed were examined. The findings show that there is a favorable correlation between the rotation speed and the rate of silver dissolution. Moreover, a very tiny concentration of di-ammonium tartrate, between 0.005 and 0.125 M, has a beneficial impact. The dissolution rate is well-affected by hydrogen peroxide concentrations between 0.05 and 0.25 M, but not significantly so in the 0.25-0.35 M range. Temperatures between 20 and 50 degrees C have a positive effect because hydrogen peroxide is stable in this range. A measurement of 25.44 kJ/mol was made of the apparent activation energy.
Keywords: Silver; Dissolution; Di-ammonium tartrate; Hydrogen peroxide; Activation energy